A termelés térbeli szétterjedése és a szervezet területi centralizációja a magyar iparban - Barta, Györgyi (Tér és Társadalom, 1987)
Two major processes formed the spatial distribution of the Hungarian industry during the 1960s and the 1970s: the spatial diffusion of the production itself and the centralization of industrial management. The decentralization process was the more apparent one from among the two: new industrial jobs were created in small- and medium-sized towns and even in large villages. The industrial development of backward areas has accelerated. Ali this had a beneficial effect on diminishing socio-economic disparities: the spatial variations in personal incomes as well as the regional differences in infrastructural supply etc. have decreased. lndustrialization, however, has evolved mainly via the enlargement of existing enterprises instead of establishing new ones. The conditions of ’extensive growth’ (i.e. the available labour) were, at the same time, less and less present. Multi-plant, multi-regional enterprises are becoming more and more prevalent in Hungarian industry. This has several, as yet hardly examined, consequences. The production functions of the enterprises are sptit among various units: the headquarters preserve the managerial and control functions while the branch-plants are usually restricted to the routine of production. Since most of the headquarters are concentrated in large cities, mainly in Budapest, the industry of the countryside is increasingly linked, in a unilateral way, to these control centres. The shortcomings of industrial location, the weak cooperation links and the dispersion of resources can also be explained, at least in part, by organizational reasons. The outmigration of skilled workers from the countryside to large urban places can also be attributed, to some extent, to similar reasons. Obviously, those settlements where ’industrial branch-plants’ are dominant, are more exposed to the adverse effects of industrial depression. The major objective of this paper was to call the attention to the spatial concentratíon of industry, to certain concurrent spatial processes which have both positive and negative impacts on spatial development.